Frieden! : Pazifistische Gedanken im Umkreis von Romain Rolland - Hertrampf, Marina Ortrud M. 1976- HerausgeberIn (Romain Rolland Studien / Études Romain Rolland, 2022)
Romain Rolland's writings on peace and humanity are still relevant in the 21st century, as they can point to ways of peaceful coexistence. However, the concept of pacifism is not entirely unproblematic in relation to Romain Rolland. His pacifism appeals first and foremost to the moral consciousness of the individual, which expresses itself in the private sphere in an understanding coexistence and friendly exchange with people of the most diverse origins and ways of thinking, and less in strategic thinking that can be translated concretely into political and social practice. Even if Romain Rolland's positions show certain contradictions and inconsistencies against the background of the changing political-ideological moods and his sometimes quite painful experiences with the intellectuals and politicians of his time, he always remained true to his deepest convictions. Romain Rolland's idiosyncratic and unideological pacifism is ultimately an expression of a profoundly humanistic will for peace. The contributions collected in this volume introduce various protagonists of war-critical pacifist discourses and explore Romain Rolland's significance for them. They also show the influence of his thought on contemporaries and personalities of subsequent generations